Effects of surface structure on soccer ball aerodynamics - Alam, F.; Chowdhury, H.; Stemmer, M.; Wang, Z.; Yang, J. (Procedia Engineering, 2012)
Soccer is the world's most popular and watched game. Due to increasing technological advancement and demand for performance, the ball manufacturers have been progressively introducing new designs since over the last decade. A traditional spherical soccer ball made of 32 stitched leather panels in 1970s has now become 8 synthetic curved thermally bonded panels. Despite being most popular game in the world, limited data is available on aerodynamic behaviour of new soccer balls especially with various surface structures and ridges. The primary objectives of this study were to evaluate aerodynamic performance of six different soccer balls which include an old vintage to current balls. The aerodynamic forces and moments were measured experimentally for a range of wind speeds in the wind tunnel. The aerodynamic forces and their non-dimensional coefficients were determined and compared. The findings indicate that the surface structure has profound effect on the flow regime around balls and their drag coefficients.